Applied GA5, GA4, and GA4/7 increase berry number per bunch, yield, and grape quality for winemaking in Vitis vinifera L. cv. Malbec. (26th November 2021) - Berli, Federico J; Alonso, Rodrigo; Pharis, Richard P; Bottini, Rubén
Abstract: BACKGROUND: The gibberellins (GAs) GA5 (inhibitor of GA3 ‐oxidase), GA4 (biologically active), GA4/7 (commercially available mixture of Ga4 and GA7 ) prohexadione‐calcium (ProCa, inhibitor of dioxygenases that render GAs bioactive, negative control), and GA3 (positive control) were applied to bunches of Vitis vinifera cv. Malbec. Different techniques, doses, and timings were used in a 3‐year field experiment. In year 1, GA5, ProCa, and GA3 were applied at 35, 20, and 0 days before veraison (DBV) by dipping bunches three times. In year 2, single applications of GA5 and GA3, also by immersion, were tested at 60, 45, and 30 DBV. In year 3, applications at 60 and 30 DBV of GA5, GA4, and a mixture of GA4/7 were evaluated by dipping or spraying the bunches. RESULTS: Vegetative growth, berry weight, and sugar content were unaffected by treatments. ProCa did not affect the yield with respect to water control, although it reduced the levels of phenolics in berry skins, an undesirable effect for winemaking. GA5, in the dose range 5–50 mg L −1, raised berry numbers, thereby augmenting bunch weight and skin phenolics at harvest, so increasing berry quality for winemaking. GA4 and GA4/7 produced similar benefits to GA5, with similar doses. CONCLUSION: The applications of GA5, GA4, and GA4/7 to developing grape berry bunches, in a range of concentrations and by dipping or spraying, increased berry numbers per bunch at harvest. The method can be used as a viticultural practice to improve the production and quality of wine grapes. © 2021 Society of Chemical Industry.